2017
DOI: 10.1080/14737140.2017.1347505
|View full text |Cite
|
Sign up to set email alerts
|

Phthalocyanine induced phototherapy coupled with Doxorubicin; a promising novel treatment for breast cancer

Abstract: Globally, breast cancer is the most common life-threatening malignant disease among women. Adjuvant chemotherapeutic treatment of anthracycline-based chemotherapy (e.g., doxorubicin) has been shown to be more advantageous over non-anthracycline-based therapies, yet possess the tenacity of developing resistance and potential side effects which have limited its use in the clinical setting. These reasons necessitate combining doxorubicin with emerging photodynamic treatment regimens. Areas covered: In this review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 55 publications
0
11
0
2
Order By: Relevance
“…We consider that future studies should focus first on the best way to deliver PDT (e.g., drug dose and targeting, light dose, multiple fibers). Much current PDT research focuses on looking for ways of increasing the selectivity of PDT between tumors and their organ of origin, such as linking photosensitizers to tumor-specific antibodies, the use of nano-carriers for photosensitizing drug delivery, the latter particularly in multidrug-resistant breast cancer, where the photodynamic effect may play a role in bypassing and inhibiting escape pathways [29][30][31]. However, we see the best potential of PDT in breast cancer in the multi-therapy setting in patients with a poor or incomplete response to NAT or in cases where NAT and surgery are not possible.…”
Section: Discussionmentioning
confidence: 99%
“…We consider that future studies should focus first on the best way to deliver PDT (e.g., drug dose and targeting, light dose, multiple fibers). Much current PDT research focuses on looking for ways of increasing the selectivity of PDT between tumors and their organ of origin, such as linking photosensitizers to tumor-specific antibodies, the use of nano-carriers for photosensitizing drug delivery, the latter particularly in multidrug-resistant breast cancer, where the photodynamic effect may play a role in bypassing and inhibiting escape pathways [29][30][31]. However, we see the best potential of PDT in breast cancer in the multi-therapy setting in patients with a poor or incomplete response to NAT or in cases where NAT and surgery are not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Ранее нами было обнаружено, что чувствительность опухолевых клеток млекопитающих разного гистогенеза, растущих in vitro, к DOX снижается в присутствии терафтала (ТФ, натриевая соль 4,5-октакарбоксифталоцианина кобальта), компонента противоопухолевого средства -бинарной каталитической системы (ТФ + аскорбиновая кислота) [32,33]. Известно, что в клинических протоколах фотодинамической терапии используются фотосенсибилизаторы фталоцианиновой природы, подобные ТФ, в комбинации с химиопрепаратами, включающей АА [34]. Принимая во внимание эти данные, мы продолжили исследования в условиях in vivo.…”
Section: оригинальные статьиunclassified
“…Доля клеток в блоке G 2 / М при концентрации DOX 2 мкМ составляет 50 % и не возвращается к контрольным величинам. Таким образом, в присутствии ТФ механизм защиты клеток меланомы линии B16 / F10 от токсичности DOX (индукция апоптоза) коррелирует с остановкой клеток в фазе G 2 / М. Такие клетки, как известно, приобретают фенотип SLC, для которого характерны морфологические (увеличение размера, разбухание ядер, появление микроядер) и биохимические (увеличение активности фермента β-галактозидазы лизосом) признаки [16,34].…”
Section: результаты и обсуждение исследование влияния тф на токсичность Dox для опухолевых клеток меланомы мышей линии B16 / F10 в системunclassified
“…Some preclinical studies and clinical trials indicated that the combination of PDT with more traditional treatments such as specific chemotherapeutic agents may become a workable anticancer strategy. 23,24 On the premise that the overall efficacy is preserved or even augmented, photo/ chemo combination therapy may allow the reduction of the dosage of individual drugs and consequently the lessening of important side effects. Mounting evidence suggested that this combination showed a prominent additive to synergistic effect over individual treatment when used alone.…”
Section: Introductionmentioning
confidence: 99%
“…With advantages of coloading, local administration and stimulus-responsive drug release, smart hydrogels may be useful in addressing drug combination regimen, thus achieving a positive outcome. 24 International Journal of Nanomedicine downloaded from https://www.dovepress.com/ by 44.224.250.200 on For personal use only.…”
Section: Introductionmentioning
confidence: 99%